Correction to: The Weibull Fréchet distribution and its applications. Issue 16 (10th December 2021) - Azimi, Reza; Esmailian, Mahdy
Abstract : Afify et al. [ The Weibull Fréchet distribution and its applications, J. Appl. Stat., 43 (2016), pp. 2608–2626] defined and studied a new four-parameter lifetime model called the Weibull Fréchet distribution. They made some mistakes in presenting the log-likelihood function and the components of score vector. In this note, we will correct them.